FosB mutant mice: Loss of chronic cocaine induction of Fos-related proteins and heightened sensitivity to cocaine’s psychomotor and rewarding effects - Hiroi, Noboru (The National Academy of Sciences of the USA, 1997)
Chronic exposure to cocaine leads to prominent, long-lasting changes in behavior that characterize a state of addiction. The striatum, including the nucleus accumbens and caudoputamen, is an important substrate for these actions. We previously have shown that long-lasting Fos-related proteins of 35–37 kDa are induced in the striatum by chronic cocaine administration. In the present study, the identity and functional role of these Fos-related proteins were examined using fosB mutant mice. The striatum of these mice completely lacked basal levels of the 35- to 37-kDa Fos-related proteins as well as their induction by chronic cocaine administration. This deficiency was associated with enhanced behavioral responses to cocaine: fosB mutant mice showed exaggerated locomotor activation in response to initial cocaine exposures as well as robust conditioned place preference to a lower dose of cocaine, compared with wild-type littermates. These results establish the long-lasting Fos-related proteins as products of the fosB gene (specifically ΔFosB isoforms) and suggest that transcriptional regulation by fosB gene products plays a critical role in cocaine-induced behavioral responses. This finding demonstrates that a Fos family member protein plays a functional role in behavioral responses to drugs of abuse and implicates fosB gene products as important determinants of cocaine abuse.